Magnetic carbon nanotubes: Carbide nucleated electrochemical growth of ferromagnetic CNTs from CO2. Issue 40 (September 2020) - Wang, Xirui; Sharif, Farbod; Liu, Xinye; Licht, Gad; Lefler, Matthew; Licht, Stuart
Highlights: CO2 is transformed to valuable magnetic carbon nanotubes incentivizing use of this greenhouse gas. The first carbide nucleated electrolytic CO2 splitting mechanism is introduced. CO2 splitting and magnetic carbon nanotube growth is facilitated by iron and nickel carbide molten carbonate electrolysis. Magnetic carbon nanotubes have a wide range of applications in medicine and catalysis. In addition to magnetic carbon nanotubes, a secondary product of the CO2 electrolysis is O2 . Abstract: This study demonstrates that CO2 can be split by molten carbonate electrolysis (1) to grow magnetic carbon nanotubes (CNTs) and (2) that the process can be initiated by carbide nucleation points acting as growth catalysts. This opens the path to other similar electrochemically prepared magnetic carbon nanomaterials. Magnetic carbon nanomaterials have a variety of applications, such as in directing medical therapy to localized regions and recoverable catalysts. In the presence of an iron or nickel containing case to house the molten carbonate electrolysis, or the presence of Fe or Ni in the electrochemical components, ferromagnetic CNTs can grow at the cathode. For example, EDS elemental analysis confirms the presence of iron in the CNTs, and XRD confirms the presence of iron carbide at the CNT nucleation site. The observed interlattice spacing of 0.20 nm of the iron carbide is distinct from the observed 0.36 nm graphene lattice spacing of the CNT walls. An excess iron release can be facilitated into the electrolyte using an iron rich alloy anode, such as Incoloy. The excess iron results in graphene layer coated iron carbide nodules on the exterior of the carbon nanotube product formed at the cathode, as well as iron carbide within these CNTs as observed by SEM and TEM.